The Affective and Learning Profiles of Students Using an Intelligent Tutoring System for Algebra - Lagud, Maria C V (Archīum Ateneo, 2010)
We investigate whether high-performing students’ experience of affect (boredom, confusion, delight, flow, frustration, neutrality and surprise) is different from that of low-performing students while using Aplusix, an ITS for Algebra. We found that students with the highest number of correct answers experienced flow the most while students with the lowest number of correct answers experienced confusion and boredom the most. Students who attempted the most difficult problems experienced flow the most while students who tried the lowest levels experienced more boredom and confusion. Students who took the longest time in solving the algebra problems experienced confusion the most while students who took the shortest time experienced confusion the least. Students who used the most number of steps to solve a problem experienced confusion and boredom the most. Students who used the least number of steps experienced more flow.